Durable and sustainable service life extension of existing concrete structures: A holistic approach within a life cycle perspective - Craeye Bart; Renne Neel; Audenaert Amaryllis; Buyle Matthias (MATEC Web of Conferences)
Concrete structures are facing increasing aging, leading to a rising demand for maintenance, repair, strengthening and/or replacement. More than 70% of the damage to reinforced concrete structures is linked to reinforcement corrosion, which can affect the durability of the structure and the residual load-carrying capacity. Actions are required which consist of an adequate diagnosis, including the identification of damage mechanisms and causes, severity and the extent of defects, showing the cause and extent of the damage, (i) to determine the actual bearing capacity, (ii) to make an estimation of the technical durability and the residual service life and (iii) to select a durable repair technique and/or maintenance strategy (pro-active vs. re-active). Furthermore, in selecting a rehabilitation strategy for preventive maintenance and curative repair, it is important to not only focus on technical requirements and initial cost, but to consider the environmental impact and financial costs over the entire life cycle and the intended service life extension, by considering LCA/LCCA. This paper highlights the entire service life extension process, from diagnosis to the assessment of both technical durability and structural load-bearing capacity, with the aim of developing durable, sustainable and economically viable repair solutions. Several case studies with different functionalities, age and damage causes are discussed: (i) a blast furnace slag cement based concrete water reservoir with insufficient post-execution curing, which led to increased carbonation, and therefore required surface protection after 15 years of service, (ii) a 60-year-old high-rise building where reinforcement scans revealed a lack of reinforcement in the balconies and incorrect placement of reinforcement, leading to reduced load-bearing capacity, and therefore required additional strengthening, (iii) a jetty with high chloride contamination and where potential mapping indicates the need of proper electrochemical treatment. By analyzing these case studies, the need for a holistic approach to concrete repair is emphasized.